DETERMINATION OF THE COMPRESSION STRENGTH RP OF MULTILAYER PLATES MADE OF SLAGOSITALS - Zdorenko, V.; Zabiiaka, N.; Sebko, K.; Gorbunova, O. (Integrated Technologies and Energy Saving, 2021)
The methodology of creating multifunctional acoustic automated devices has been further developed, it is based on the construction of simple algorithms for transforming and processing signals of measuring instruments. A differential acoustic method for controlling the physical and mechanical parameters of multilayer plates made of slag glass-ceramics has been investigated. A structural diagram of an automated device for measuring acoustic control of the ultimate compressive strength Rр of a controlled slag glass-ceramics plate is proposed. The option of automation of the measurement process considered in the article makes it possible to carry out measuring control of the strength characteristics for a relatively short period of time and by averaging the results of measurements of the physical and mechanical parameters of slag glass-ceramic plates, leads to a decrease in the values of random measurement errors and thereby contributes to an increase in the accuracy of measurements of physical and mechanical parameters of slag glass-ceramics products. The values of the relative increments of the attenuation coefficient ∆ƞ23/ƞ4were obtained, while the ranges of the values of the attenuation coefficient of a transmission of various waveforms of the piezoelectric transducer correspond to the ranges of the compressive strength Rр of the test sample. At the same time, the control of the strength of the material Rр at multiple frequencies is due to the fact that even a slight change in the geometric parameters of the slag glass-ceramics slab leads to a change in the generalized parameters of the universal transformation functions of the measuring differential acoustic devices, which are associated with the physical and mechanical characteristics of the controlled material of the sample The proposed two-parameter differential acoustic control method allows to  keep in mind the linkage between temperature and mechanical parameters: the unequal distribution of the temperature along the length of the sample and the uneven distribution deformation  of temperature with the localization of this plastic component in the middle part of the slag glass-ceramics plate, which is most significantly affected by temperature and, as a consequence, is subject to gradual destruction.